1986
DOI: 10.1159/000226101
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Harvey-<i>RAS</i> Oncogene Expression with Conventional Clinicopathologic Parameters of Breast Cancer

Abstract: We have previously examined the expression of the Harvey-ras (Ha-ras) oncogene related transcripts in human malignant breast tumors and in their respective normal tissue [Spandidos and Agnantis, Anticancer Res. 4: 269–272, 1984]. Our results revealed a significant elevation of Ha-ras transcripts in malignant compared to normal tissue. In the present follow-up study we have examined the relationship of Ha-ras oncogene expression to the various clinicopathological parameters of these tumors. Although elevated ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…Similarly, no trend between p21 levels and tumour size was detected. This is in agreement with Agnantis et al [30], who also found no correlation between H-ras mRNA transcripts and T stage. In contrast, others have reported that advancement of T stage correlates significantly with an increase in p21 levels [18,28].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, no trend between p21 levels and tumour size was detected. This is in agreement with Agnantis et al [30], who also found no correlation between H-ras mRNA transcripts and T stage. In contrast, others have reported that advancement of T stage correlates significantly with an increase in p21 levels [18,28].…”
Section: Discussionsupporting
confidence: 93%
“…The evidence that changes in the structure and expression of par ticular transforming cellular gene sequences, referred to as oncogenes, contribute to the genesis of tumors is often based on the observation that these genes are rearranged or amplified. Preliminary investigations on a molecular level showed alterations of several known oncogenes in human breast cancer: a new FxoRI re striction fragment was observed for c-mos [1], c-myc was found to be amplified and overexpressed [2], a significant elevation of Ha-ras transcripts was cor related to some clinicopathological parameters [3], and loss of Ha-ras alleles in aggressive breast tumors was reported [4], Most recently, relapse and survival in correlation to erbA, erbB-1 and erbB-2 status were analyzed in mammary carcinoma [5][6][7]. Whereas the protein coded by v-erbA is related to the tyrosine receptor [8], v-erbB codes for a protein similar to the cytoplasmic portion of the epidermal growth factor receptor (F.GFR).…”
Section: Introductionmentioning
confidence: 99%
“…Agnantis etal. [49] found a significant elevation of Ha-ras transcripts in malignant compared to normal breast tissue, with a higher mean value of expression in cases with lymph node metastases. Hand et al [51] immunologically assayed the Ha-ras P21 protein in samples of human breast carcinoma and colon carcinoma.…”
Section: Oncogene Expression Correlation With Human Tumor Metastatic mentioning
confidence: 81%